Association between nighttime sleep duration, sleep timing and falls among middle‐aged and older Chinese population: A cross‐sectional analysis from the Dongfeng–Tongji cohort study, China. Issue 11 (8th February 2017) - Wang, Yi; Li, Wending; Shen, Lijun; Song, Lulu; Li, Hui; Liu, Bingqing; Yuan, Jing; Wang, Youjie
Abstract : Aim: To examine the association between nighttime sleep duration, sleep timing, and their interactive effect on falls among middle‐aged and older Chinese adults. Methods: The study sample of 35, 465 (mean age 64.5 years) subjects were from the Dongfeng–Tongji cohort. All subjects completed baseline questionnaires and medical examinations. Participants were classified into five groups based on nighttime sleep duration: <7 h, 7– ≤ 8 h, 8– ≤ 9 h, 9– ≤ 10 h, ≥10 h, and three groups based on sleep timing: <21:00, 21:00– ≤ 23:00, ≥23:00. Logistic regression models estimated the odds ratios (ORs) of nighttime sleep duration/timing with single/recurrent falls. Results: The one year rate of falls was 15.2 % among the subjects. After adjusting for potential confounders, participants with longer sleep duration (≥10 h) had 1.48 times (95 % confidence interval [CI], 1.11–1.97) higher odds of recurrent falls, compared with those sleeping 7– ≤ 8 h. Earlier (<21:00) and later (≥23:00) sleep timing were associated with recurrent falls (earlier: OR 1.90, 95 % CI 1.33–2.73; later: OR 1.33, 95 % CI 1.14–1.56) compared with a normal sleep schedule (sleep during 21:00– ≤ 23:00). The combined effect showed that longer sleep duration and earlier sleep timing were associated with a greater occurrence of falls (OR 1.66, 95 % CI 1.22–2.26). Conclusions: Long nighttime sleep duration was associated with a higher occurrence of recurrent falls but not with a single fall. Long sleep duration with early timing greatly increased both single and recurrent falls.Geriatr Gerontol Int 2017; 17: 1886–1892 .